Thingiverse: review and analysis of available files. (2018) - Baumann, Felix W.; Roller, Dieter
This paper aims to present an overviewof the Thingiverse digital model repository and provides an analysis of a subset of randomly selected models of this site. To carry out this study, literature research was conducted to identify relevant works. Based on existing research, a subset of available models is acquired and analysed utilising existing open source software. Focusing on the geometrical details of the acquired models, an analysis is performed. Furthermore, statistical data such as download, view counters, and utilised licences of these models, is collected. For the literature review on this platform, 25 existing works were identified. From the 10, 000 randomly selected ThingIDs, 3528 were existent and were acquired. Most metrics calculated are dominated by less than 20% of all the analysed models. Online repositories are a source for user-generated digital models. This paper suggests that the licence of choice is a creative commons – attribution – share alike licence.